Text and picture integration during bridging information processing: A comparison of English and Chinese L1 and L2 speakers. - Zhang, Chenyi; Tsimpli, Ianthi; Schmidt, Elaine (Memory & Cognition, 2025)
Bridging information facilitates comprehension in both textual and pictorial stories, but its effects when both types of information are present remain unclear. This study examines how bridging information and individual differences influence comprehension across texts and pictures. Participants read four-segment stories under six conditions: 1) picture-original (pictorial stories), 2) picture-to-text-switch (pictorial stories with textual bridging information), 3) picture-missing (pictorial stories without bridging information), 4) text-original (textual stories), (5) text-to-picture-switch (textual stories with pictorial bridging information), and (6) text-missing (textual stories without bridging information). L1 and L2 Chinese and English speakers participated. Missing conditions led to longer comprehension times across all groups, confirming the facilitative role of bridging information. Crucially, the picture-to-text switch caused no disruption, and Chinese L1 speakers were unaffected by the text-to-picture switch, suggesting that bridging information can be processed during text and picture integration without extra cognitive resources. However, English L1 and L2 speakers, as well as Chinese L2 speakers, showed increased comprehension times in the text-to-picture switch condition, indicating greater processing difficulty for alphabetic and L2 texts. Robust effects of individual differences were also revealed.